Adalimumab in Elderly Patients with Non-Infectious Uveitis. Safety and Efficacy. (17th November 2021) - Moll-Udina, Aina; Miguel Escuder, Lucía; Hernanz, Inés; Llorenç, Victor; Fonollosa, Alex; Cordero Coma, Miguel; Sainz de la Maza, Maite; Espinosa, Gerard; González Guijarro, J. Jacobo; Lopez Lopez, Fernando; Alba-Linero, Carmen; Hernández, Marisa; et al.
ABSTRACT: Purpose : To assess the efficacy and safety of adalimumab in elderly patients with noninfectious uveitis (NIU). Methods : An observational, retrospective, multicenter study was done. Changes in best-corrected visual acuity (BCVA), inflammatory activity parameters, central retinal thickness (CRT), and the occurrence of adverse events (AE) developed during follow-up were recorded. Results : A total of 82 eyes from 41 patients 60 years of age and older with noninfectious uveitis treated with adalimumab were included. A significant improvement in BCVA (71.5 to 75.4 letters, p = .001) and in CRT (311.1 μm to 265 μm, p = .001) was observed. Moreover, a significant decrease from baseline in the rate of patients with anterior chamber cell (ACC) >0+ (34.6% to 5.7%, p = <0.001) or vitreous haze>0+ (21.3% to 4.3%, p = .002) was determined. AEs were observed in 11 patients (26.8%). Conclusion : Adalimumab can be safe and efficacious for the treatment of NIU in patients 60 years of age and older.